School Heads’ Competence, Teachers’ Performance in the Light of Philippine Professional Standards for Teachers, and Students’ Academic Performance - Estrada, Mary Joy; Gumban, Joey (Technium Sustainability, 2024)
School heads' competence and teachers' performance play vital roles towards the school's overall performance which includes the students' academic performances. Hence, the purpose of this study was to find out the factors which influenced teachers' ratings and students' academic performances. This descriptive-comparative-correlational research design aimed to investigate the level of school heads' competence, teachers' performances, and students' academic performances, the difference of students' academic performances according to sex, socio-economic status and parents' educational attainment, and relationship between the variables. The study was conducted to 180 Grade 6 students of the Division of Cadiz City. Mean and standard deviation were used for descriptive analysis, Mann-Whitney, Krustal Wallis, and Welch Anova Test for comparative analysis, and PPM Person Product Moment of Correlation was utilized to determine relationship among variables. Self-made questionnaire based from the domains of the PPST was used. The results revealed that females outperformed males, also, there's a gap between the students' academic performances whose parents are college and elementary graduates. Furthermore, there was no significant difference shown in the students' academic performance when grouped according to socio-economic status. Also, there was a significant relationship between the school heads' competence and teachers' performance while no significant relationship between teachers' and students' academic performance was found. In conclusion, learner's gender and parents' education influence students' academic performance while socioeconomic status revealed no significance on students' performances. Moreover, school heads' competence is a factor in the teachers' performance while teachers' performance showed no relation to the learner's academic achievements in schools.